The pros and cons of hystero-preservation on pelvic reconstructive surgery - Chin- Chiu Chen; I- Ting Peng; Ming- Ping Wu (Wolters Kluwer Medknow Publications, 2023)
In the "boat at the dock" theory, pelvic organ prolapse (POP) may happen when the ropes (uterine supportive ligaments) break and/or the water level drops (pelvic floor muscles). Thus, it causes the boat (uterus and other pelvic organs) to slip from normal position and protrude out of the vagina. Surgical intervention with or without hysterectomy (hystero-preservation) is the most effective treatment for POP. Both hysterectomy and hystero-preservation for POP had a high anatomic and clinical cure rate. There is an increasing trend of hystero-preservation for POP during the past decades. The choices of either hysterectomy or hystero-preservation depend on the surgical factors, psychosocial factors, self-esteem and sexuality factors, and surgeon factors. Pelvic reconstructive surgery, either hysterectomy or hystero-preservation, can be performed via different approaches, including abdominal, laparoscopic, and vaginal routes, with native tissue or with mesh. This review will elucidate their related pros and cons, with further discussion and comparison of hystero-preservation via different routes.